Canadian Gender-Based Violence Prevention Programs: Gaps and Opportunities - Chen, YiMin (Violence against women, 2025)
Gender-based violence (GBV) prevention programs have long played an important part in both teaching the realities of GBV and training people in techniques to avert, mitigate, and respond to violence. This article examines the current state of GBV prevention training in Canada through an analysis of 81 GBV education programs provided by antiviolence organizations and universities. We identified notable gaps in topics relating to technology-facilitated violence and abuse in programs targeting men and in the provision of bystander intervention training. Each of these areas represents important, but as yet unrealized, opportunities in violence prevention.